Non-Coaxially Rotating Motion in Casson Martial along with Temperature and Concentration Gradients via First-Order Chemical Reaction - Noman Jabbar (MDPI AG, 2021)
The effect of non-coaxial rotation on the transport of mass subjected to first-order chemical reaction is studied analytically. The effects of thermal radiation, buoyancy, constructive and destructive chemical reactions along with Casson fluid in rotating frame are discussed. Time evolution of primary and secondary velocities, energy and solute particles are analyzed. The behavior of flow under the variation of intensity of magnetic field is also investigated. Evolutionary behavior of primary velocity is opposite to the evolutionary behavior of secondary velocity. The impact of buoyant force on primary velocity is opposite to the role of buoyant force on the secondary velocity. The evolutionary behavior of temperature is also examined and a remarkable enhancement in temperature is noticed. Thermal radiation causes the fluid to be cooled down as heat energy is escaped by thermal radiation. Evolutionary behavior of concentration is also analyzed and an increasing of concentration versus time is noted. Destructive chemical reaction results a remarkable reduction in the concentration and vice versa for generative chemical reaction.